2020
DOI: 10.1016/j.heliyon.2020.e04532
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression in the lungs of a mouse model of sepsis induced by cecal ligation and puncture

Abstract: Circular RNAs (circRNAs) are novel endogenous RNAs with vital roles in the pathology of various diseases. However, their role in sepsis-induced lung injury is unknown. In this study, high-throughput gene sequencing was used to analyze the expression profiles of circRNAs in lung specimens of mice grouped by acute lung injury induced by cecal ligation and puncture (CLP) and sham. To identify differentially expressed circRNAs, the left lungs of sham ( n = 3) and CLP ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Some miRNAs have been reported to regulate inflammation; for example, miRNA-208-5p regulates myocardial injury in septic mice [ 44 ], and miRNA-29 promotes pancreatic β cell inflammation via TRAF3 [ 45 ]. CircRNAs or lncRNAs, which act as miRNAs, were significantly differentially expressed in the ALI group in this study and the previous study of ALI [ 46 , 47 ]. It has also been recognized that circANKR inhibits the NF-κB signaling pathway by acting on the miR-31/MyD88 axis [ 48 ], and lncRNA TUG1 also alleviates sepsis-induced acute lung injury by targeting miRNA-34b-5p [ 49 ].…”
Section: Discussionsupporting
confidence: 76%
“…Some miRNAs have been reported to regulate inflammation; for example, miRNA-208-5p regulates myocardial injury in septic mice [ 44 ], and miRNA-29 promotes pancreatic β cell inflammation via TRAF3 [ 45 ]. CircRNAs or lncRNAs, which act as miRNAs, were significantly differentially expressed in the ALI group in this study and the previous study of ALI [ 46 , 47 ]. It has also been recognized that circANKR inhibits the NF-κB signaling pathway by acting on the miR-31/MyD88 axis [ 48 ], and lncRNA TUG1 also alleviates sepsis-induced acute lung injury by targeting miRNA-34b-5p [ 49 ].…”
Section: Discussionsupporting
confidence: 76%
“…Acute respiratory distress syndrome (ARDS) or ALI is a devastating disease characterized by dysregulated immune responses, endothelial activation, and microvascular thrombosis [ 11 ]. Recently, several circRNAs have been identified to regulate the inflammatory response and cell apoptosis of pulmonary ECs through downstream miRNAs [ 12 ]. In the present study, we performed transcriptomic profiling to evaluate the expression of circRNAs in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a family of noncoding RNAs presenting crucial roles in regulating normal physiology and pathological developments. Several studies using systemic approaches and/or bioinformatics analysis all evidenced an altered expression profile of circRNAs in ALI (Bao et al, 2019;Li et al, 2019;Yuan et al, 2020;Jiang et al, 2020b), supporting their importance in ALI development. In contrast, the mechanistic understanding of specific circRNAs in ALI is still in its infancy (Zou et al, 2020;Yang et al, 2021) and largely remains to be revealed. To expand our understanding of circRNAs in ALI, we followed up on circEXOC5 (hsa_circ_0004399), one of the most significantly up-regulated circRNAs identified by microarray and verified by qRT-PCR in lung macrophages from CLP mice as compared to those from sham-operated mice (Bao et al, 2019).…”
Section: Introductionmentioning
confidence: 90%